Diminished DEFA6 Expression in Paneth Cells Is Associated with Necrotizing Enterocolitis. (21st October 2018) - Markasz, Laszlo; Wanders, Alkwin; Szekely, Laszlo; Lilja, Helene Engstrand
Abstract : Background . Necrotizing enterocolitis (NEC) is the most common gastrointestinal disorder in premature infants with a high morbidity and mortality. Paneth cell dysfunction has been suggested to be involved in the pathogenesis of NEC. Defensin alpha-6 (DEFA6) is a specific marker for Paneth cells acting as part of the innate immunity in the human intestines. The aim of this study was to investigate the expression of DEFA6 in infants with NEC. Materials and Methods . Infants who underwent bowel resection for NEC at level III NICU in Sweden between August 2004 and September 2013 were eligible for the study. Macroscopically vital tissues were selected for histopathological evaluation. All infants in the control group underwent laparotomy and had ileostomy due to dysmotility, and samples were taken from the site of the stoma. DEFA6 expression was studied by immunohistochemistry. Digital image analysis was used for an objective and precise description of the samples. Results . A total of 12 infants were included in the study, eight with NEC and four controls. The tissue samples were taken from the colon (n = 1 ), jejunum (n = 1 ), and ileum (n = 10 ). Both the NEC and control groups consisted of extremely premature and term infants (control group: 25–40 gestational weeks, NEC group: 23–39 gestational weeks). The postnatal age at the time of surgery varied in both groups (control group: 4–47 days, NEC group: 4–50 days). DEFA6 expression in the NEC group was significantly lower than that in the control group and did not correlate with gestational age. Conclusion . The diminished DEFA6 expression in Paneth cells associated with NEC in this study supports the hypothesis that alpha-defensins are involved in the pathophysiology of NEC. Future studies are needed to elucidate the role of alpha-defensins in NEC aiming at finding preventive and therapeutic strategies against NEC.